2017
DOI: 10.1590/1414-431x20175837
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vacuum sealing drainage on the treatment of cranial bone-exposed wounds in rabbits

Abstract: This study was designed to assess the efficacy of vacuum sealing drainage (VSD) on skull exposure wounds in rabbits and to investigate the underlying mechanism of the process. Full-thickness excisional circular wounds 2×2 cm with or without periosteum involvement were created in 88 New Zealand white rabbits (mean body weight: 3.0±0.65 kg). Animals were randomly divided into 4 groups: periosteum-intact wounds treated with traditional dressing (p+control), periosteum-intact wounds treated with VSD (p+VSD), perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…VSD promotes angiogenesis by increasing the quantity and quality of collagen. [ 19 ] Additionally, VSD can increase the expression of transforming growth factor β1 (TGF-β1), which will promote granulation tissue growth and contribute to wound healing. [ 20 ] The duration of antibiotic use in the VSD group was lower than in the traditional group.…”
Section: Discussionmentioning
confidence: 99%
“…VSD promotes angiogenesis by increasing the quantity and quality of collagen. [ 19 ] Additionally, VSD can increase the expression of transforming growth factor β1 (TGF-β1), which will promote granulation tissue growth and contribute to wound healing. [ 20 ] The duration of antibiotic use in the VSD group was lower than in the traditional group.…”
Section: Discussionmentioning
confidence: 99%
“…NPWT has been shown to promote tissue granulation and decrease wound volume by debriding devitalized tissue, promoting blood flow and tissue perfusion, decreasing bacterial colonization, and removing excess serous fluid 1,5,12,13 . However, in my experience of this and previous cases, patients report pain and discomfort throughout the NPWT treatment period; two required opioid medications for pain control.…”
Section: Discussionmentioning
confidence: 82%
“…Some studies have shown that adding medication irrigation, such as ozonated water and recombinant human epidermal growth factor, could accelerate wound healing [ 18 , 19 ]. Animal experiments have shown that VSD can effectively promote wound healing by increasing the vessel density with hydroxyproline content, reducing the inflammatory responses and generating an ordered collagen arrangement [ 20 ]. Compared with traditional wound debridement and dressing changes, VSDs theoretically have the potential to reduce the frequency of dressing changes, shorten the healing time, and increase the success rate of wound healing.…”
Section: Discussionmentioning
confidence: 99%